The global problem of land degradation and desertification - Kertész, Ádám (Hungarian Geographical Bulletin, 2009)
It’s a well known fact that land(scape) degradation is an ensemble of negative processes extending over immense areas. The methodologies of physical and social geography are the best tools for the investigation of land degradation processes, due to the complex nature of these processes. It is well known that environmental factors contribute to land degradation processes. Socio-economic factors and the role of human society is equally important, and in some cases, even more important, than natural factors. Degradation processes within subhumid, semi-arid and arid areas are defi ned as desertification processes to draw attention to the specific dangerous situation in these areas. Hungary signed the Convention on Desertification, as increasing aridity is a real national danger, especially on the DanubeTisza interfluve. There are areas in Hungary corresponding to desertification definitions. Thus, desertification research is an important challenge for Hungarian geography.